Jurisprudência e racionalidade: o precedente judicial como elemento de coerência do sistema jurídico brasileiro - Alencar, Mário Soares de (2018)
The mainpurpose of this study is to make feasible the study of the use of precedents in the reasoning of judicial decisions within the Brazilian legal system, considering that the issue grows in importance with the entry into force of the new Code of Civil Procedure, which established a disciplinary of legally binding precedents. In fact, over the years, reference to precedents in the grounds of judicial decisions has become common in the national legal system, although it is inherited from the Roman-German legal tradition, in which law prevails as the primary source of normativity. Notwithstanding the doctrinal controversy over the possibility or legal suitability of extracting normative elements from judicial decisions to determine the fate of future cases, giventhe principle of legality inherent in the Brazilian constitutional system, it is undeniable that thepracticeoflawhasalwayshadasrelevantreferencetothejurisprudenceof the courts in one direction or another, as firm support to justify demands or to substantiate decisions. On the other hand, the lack of a theoretical reference for understanding the role of judicial precedentin the justification of judicial decisions renderedin the legal environment of the civil law tradition, along with legal and constitutional normative elements, makes it necessary to study how this use and structure a theory that identifies the legal nature and the role played by precedents in this field.If legal experience shows that the use of precedents in the foundation of new judgments is a constant practice in the Brazilian legal system, it is essential to understand this practice scientifically, presenting, in addition to the mere normative conformation, especially in view of the discipline established by the new Code of Civil Procedure, the theoretical-scientific bases that justify the reference and necessary linkage to previous judicial decisions,verifying the consequences of this process for the constitutional legal order.With this aim, the research focused on the review of national and foreign bibliography on the subject, especially regarding the foundations used to justify the normative reflexes of the previous one in future cases, seeking to evidence both its consistency and its points of theoretical fragility. As support for the analysis of legal rationality, the research revolved some epistemological assumptions of Law, revisiting the themesof truth and objectivity of legal knowledge. In this sense, Ronald Dworkin was used as a theoretical reference, exploring the coherentist epistemological basis underlying his theory of law as integrity and his thesis about the possibility of a correct answer in law.The study indicated the insufficiency of the purely formal, deontological and pragmatic foundations for the justification of the use of judicial precedents in the national legal system, evidencing the need to adopt a coherentist epistemologicalmodel, replacing traditional foundationalism. In this line, the judicial precedent becomes a normative element that contributes to the coherence of the legal system, allowing the analysis of the rationality of the responses of the legal system to practical problems.